Stability of rank two Ulrich bundles on projective K3 surfaces - Casnati, Gianfranco; Galluzzi, Federica (MATHEMATICA SCANDINAVICA, 2018)
Let FP^N be a K3 surface of degree 2a, where a2. In this paper we deal with Ulrich bundles on F of rank 2. We deal with their stability and we construct K3 surfaces endowed with families of non-special Ulrich bundles of rank 2 for each a2.